Penentuan Alternatif Strategi Pengembangan Sopi Lokal Kabupaten Timor Tengah Utara (Studi Kasus Desa Letmafo Timur) - Yohanes Pebrian Vianney Mambur; Lambertus Nesi Bria (Fakultas Pertanian, Universitas Timor, 2022)
Sopi Timor is known as a symbol of intimacy, togetherness, and kinship. In addition, sopi is also known as the civilization of the people of West Timor in social reality and as a household business that was carried out approximately 300 years ago. The purpose of this research is to find out alternative strategies for developing local sopi. The method of analysis in this study is the SWOT matrix. The results showed that local sopi is in quadrant I, which means attacking by promoting local sopi on a large scale because the products produced are very good and consumers like them. This research also contains 9 alternative strategies with 4 priority strategies for local sopi development, namely: 1) utilizing the availability of raw materials and business experience to answer market demand; 2) the ease of selling their products by utilizing a supportive location and supporting government policies; 3) utilize existing manpower and technology to capture market opportunities; 4) retaining customers by taking advantage of innovations and the ease of selling their products can patent local sopi products produced by producers.